Characterization of the Points of $ϕ$-Strong Summability of Fourier–Laplace Series for Functions of the Class $L_p(S^m),\; p > 1$ - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider the behavior of the ϕ-strong means of Fourier–Laplace series for functions that belong to $L_p(S^m),\; p > 1$, on a set of points of full measure on an $m$-dimensional sphere $S^m$.